PENGARUH REPUTASI UNDERWRITER, REPUTASI AUDITOR, DAN RETURN ON ASSET TERHADAP FENOMENA UNDERPRICING PADA INITIAL PUBLIC OFFERING DI BURSA EFEK INDONESIA - Taufika Dian Hartono; Nurfauziah Nurfauziah (Universitas Bunda Mulia, 2020)
Initial Public Offering (IPO) is the company’s activity issuing its share for the first time to the public in order to increase the company’s capital. This research is aimed to know the influence of underwriter reputation. Auditor reputation, and Return On Asset (ROA) againts underpricing for period 2012-2016. This research was conducted using multiple regression analysis with 5 percent level of signification. The aim of the research is to know the influence of each variable. Before using multiple regression tet, the author tested the classical first. The result of this research againts the variable is ROA has a significant positive effect on underpricing and other variable that is the underwriter reputation and auditor reputation are not affected againts underpricing. Key word : Underpricing, Underwriter Reputation, Auditor Reputation, ROA